Torulisquama Zhang & Li (Lepidoptera: Crambidae) in China, with a discussion on its distribution based on climatic variables. (2nd July 2020) - Jie, Lu-Lan; Yang, Jing-Bo; Li, Wei-Chun
ABSTRACT: A taxonomic study of Torulisquama Zhang & Li was conducted. Its geographical distribution pattern in China is analysed with MaxEnt and ArcGIS based on known localities and 19 environmental variables. The results suggest that the most suitable areas for the genus are located in Southeast China, and the minimum temperature of the coldest month (Bio6) is revealed to the most important variable affecting the present distribution pattern. The suitable ranges of Bio6 are between −7.9°C and 7.9°C. Furthermore, we add a new species Torulisquama lini Jie & Li, sp. nov . to the genus from Jiangxi Province of Southeast China. A map showing the geographical distribution pattern of Torulisquama in China is provided. Image of habitus and genitalia of the new species is illustrated, along with a checklist and a key of the genus. http://www.zoobank.org/urn:lsid:zoobank.org:pub:B0B41A20-43F0-4ECF-A0BC-C94CC99A09D8